Virtual reality as narrative medium: The emotional effects of full immersion in VR-based film Aladin - Arvina Dwi Romadhani (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
Virtual Reality (VR) has emerged as a transformative medium, offering immersive storytelling experiences compared to traditional 2D films. This study aims to compare emotional and physiological responses elicited by Virtual Reality (VR) and Youtube (YT) versions of Aladin: Escape the Cave of Wonders. Using a mixed-methods approach, emotional data were collected through PANAS (Positive and Negative Affect Schedule), while physiological responses such as skin temperature (SKT), heart rate (HR), and respiratory patterns were recorded. Results indicate that VR elicits stronger emotional engagement, with significant increases in negative affect (e.g., fear and nervousness) and higher HR compared to YT films. Scene-specific analyses reveal that immersive environments amplify emotions during intense scenes, supported by physiological markers of heightened arousal. This study underscores VR’s potential as a narrative medium and provides insights into its application for enhancing audience engagement across genres.